Múltiplas leituras: novas perspectivas teóricas e metodológicas para um letramento literário - Sugayama, Ariane Mieco (2017)
When reading is linked to a monological teaching-learning model, it silences the interpretive voice and marginalizes the reader’s subjectivity. In contrast to this approach, the Think Aloud in Group literacy practice, which is being built by the teachers and researchers in the GEIM research group, seeks to transform the teaching practices as well as the reading identity of their students (QUEIROZ, 2009; TAVARES DOS SANTOS, 2013; among others). The Think Aloud in Group is a dialogical and collaborative literacy practice that aims to provide space to the voice and the subjectivity of readers so that they can share, negotiate, co-construct and evaluate the different meanings of the text in face-to-face interaction (ZANOTTO, 2014a). As a result of the reader’s protagonism, the occurrence of multiple interpretations is possible because each reader can position him/herself in an active and responsive manner regarding the text. For the teacher, working with multiple interpretations has been challenging since the dominant sociocultural model within the school context is of single reading. Thus, the study of multiple text readings is the focus of this thesis, aiming to contribute to the transformation of literary reading teaching. The goals of this study, inserted in the Applied Linguistics area, are: 1) investigate the multiple interpretations of figurative language and the gaps/silences in the short story A Moça Tecelã [The Weaving Girl] (COLASANTI, 2004); 1.2) analyze the socio-cognitive processes involved in the co-construction of multiple readings. The study’s questions are: 1) What were the multiple interpretations of the literary text? 1.1) What are the socio-cognitive processes involved in the co-construction of the multiple interpretations? 2) In which aspects can the investigation of the sociocognitive processes, involved in the co-construction of the multiple interpretations, contribute to literary literacy? This qualitative study (DENZIN; LINCOLN, 2006) has an interpretative orientation (MOITA LOPES, 1994); the research strategy adopted is the instrumental case study. The theoretical basis is related to studies about literacy and literature, the teaching of literature, cognition involved in the interpretation of figurative language, and epistemology of language and communication. The methodological instruments used were: 1) The Think Aloud in Group as method facet; and 2) the reading diary. The subjects of the study were four readers, whose professions are related to reading and to children and young adult literature. The results obtained revealed the co-construction of five readings for the story, which were partially explained through the Parable Theory (TURNER, 1996) and the Theory of Conceptual Blending (FAUCONNIER; TURNER, 2002). However, the data highlighted the readers’ cognitive operations; for example, several inferential rationale involved in the interpretation of figurative language, which were explained in the studies by Zanotto (2010) and Moura; Zanotto (2009). As to the contribution of this study for literary literacy, the data obtained revealed that there was a reflexive comprehension of language figures and of gaps in the text